PHARMACOLOGICAL SUPPORT TREATMENT OF NON-SUICIDAL SELF-INJURIES AMONG CHILDREN AND ADOLESCENTS: A NARRATIVE REVIEW - Jakub Rogalski; Tomasz Tomczak (Health Problems of Civilization)
Non-suicidal self-injuries (NSSI) constitute a significant problem among children and adolescents, especially during the global burden of mental disorders worldwide. Moreover, such behaviors are perceived as a risk factor for the suicidal behaviors occurrence in the future. Thus, it would appear necessary to search for effective forms of their treatment. A pharmacological approach may play a supportive role. This study is a narrative review summarizing scientific reports on possible pharmacological support treatment of NSSI among children and adolescents. Internet scientific bases were searched for literature, including original research, review articles and case reports. There are many possible pharmacological interventions that may reduce the incidence of self-harm behaviors. Antihistamines and neuroleptics can be used successfully in the acute phase. In turn, second-generation antipsychotics and potentially naltrexone seem to be the most effective in long-term treatment. Although psychotherapy is the basic form of NSSI treatment, a psychopharmacological approach may play an essential role in reducing the incidence of self-harm behaviors. Nevertheless, the use of psychotropic medications is prohibited in most cases and may be limited due to their side effects. Moreover, there is a need to validate their efficiency in next studies to gather strong evidences concerning their widespread use.